Knowledge and attitude towards contraception among undergraduate students school of Health Sciences, Universiti Sains Malaysia - Imran, Norzianah Mohd (Universiti Sains Malaysia, 2024)
Contraception is widely used to prevent unplanned pregnancies, unsafe abortions and sexually transmitted infections (STIs). Despite awareness about contraception usage, young adults lack adequate knowledge regarding its usage. This study aimed to assess the level of knowledge and attitudes towards contraception among undergraduate students at the School of Health Sciences, Universiti Sains Malaysia (USM). A cross-sectional study was conducted from 1st January 2024 to 28th February 2024 at the School of Health Sciences, USM. A total of 214 undergraduate students were recruited via a stratified and simple random sampling method. A pre-tested questionnaire was used to assess participant demographic characteristics, knowledge levels and attitudes towards contraception. Descriptive analysis and Pearson chi-square test were used to analyze data. This study found that the majority of participants were Malay (76.7%), female (76.6%), and from nuclear families (73.8%), with over half living in urban areas (58.4%) and had moderate knowledge (47.2%) and attitude (47.7%) towards contraception. Gender (p=0.001) and year of study (p=0.028) were associated with knowledge level towards contraception. A significant association was found between year of study (p=0.001) and area of residence (p=0.001) with attitude level. Knowledge level was significantly associated with attitude level (p=0.008). This study indicates a need to elevate and refine students’ understanding and outlook on contraception, ensuring they possess greater knowledge and a more supportive stance towards contraception.